Significados dos atendimentos psicossociais on line para a saúde mental de estudantes universitários no contexto da pandemia de Covid-19 no município de Belém-Pa - MONTEIRO, Evanildo Lopes (2023)
Universities have dropout / dropout rates, for numerous reasons, and here the COVID19 pandemic stands out, with the emergence of psychosocial problems, due to social isolation, economic crisis and emotional instability, for fear of the future, the feeling of insecurity, from the death of relatives and friends and the feeling of powerlessness in the face of events in society due to the consequences for human health and its social context (Dias Sobrinho, 2010). In this way, many students need psychosocial care during the COVID-19 epidemic and post pandemic. This research aims to identify the meanings of remote psychosocial care through ICTs for university students in the municipality of Belém/PA in the context of the COVID-19 pandemic. From the services performed remotely in the Extension Project linked to the Navega Saberes Notice of PROEX-UFPA. Data analysis was carried out through Phenomenology, the interviews were transformed into texts and after reading and rereading them, the Units of Meaning that were described in the results were identified. It was noticed that in the pandemic context, stress and anxiety form the main symptoms emerged among university students and that through the actions of the Psychosocial Care Project, it was observed that each person learned and reflected on himself and the context that the fence, seeking better adjustments and changes that offer the possibility of meaning.